Double Spaced: Abstract Labour in Urban Kampung - Newberry, Jan (Anthropologica, 2022)
Although kampung means village in neighbouring Malaysia, in Indonesia, it refers to dense neighbourhoods in cities. These neighbourhoods represent a community form reproduced through governance across various regimes but also through daily exchanges and support between inhabitants. Based on fieldwork in Yogyakarta, central Java, this paper considers the form of labour represented by these spatial enclaves and its connection to the reality of a community form produced both through administration as well as a local structure of feeling. The relationship of these imagined communities to questions of abstract labour is considered along with their relevance for contemporary urban anthropology.